2022
DOI: 10.1001/jamanetworkopen.2022.28518
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Maternal Antenatal Corticosteroid Treatment and Psychological Developmental and Neurosensory Disorders in Children

Abstract: IMPORTANCE Corticosteroids administered to women at risk of imminent preterm birth is one of the most effective ways to improve the prognosis of infants born preterm. Scant data about longterm neurodevelopmental and neurosensory outcomes among the treatment-exposed children are mixed, suggesting that not all domains of neurodevelopmental and neurosensory function may be equally affected. Moreover, the long-term outcomes may vary according to whether the treatmentexposed children are being born preterm (<37 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…5,6 In studies considering longer-term neonatal follow-up, exposure to antenatal corticosteroids has been associated with differences in childhood neurocognitive development, particularly when delivery occurs at term. [9][10][11] In some studies, exposure to antenatal corticosteroids has also been found to increase maternal infection morbidity. 6 These findings raise concerns that the American College of Obstetricians and Gynecologists guidelines recommending antenatal corticosteroid administration in the late-preterm period for those at risk for preterm delivery may not be universally appropriate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In studies considering longer-term neonatal follow-up, exposure to antenatal corticosteroids has been associated with differences in childhood neurocognitive development, particularly when delivery occurs at term. [9][10][11] In some studies, exposure to antenatal corticosteroids has also been found to increase maternal infection morbidity. 6 These findings raise concerns that the American College of Obstetricians and Gynecologists guidelines recommending antenatal corticosteroid administration in the late-preterm period for those at risk for preterm delivery may not be universally appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 In studies considering longer-term neonatal follow-up, exposure to antenatal corticosteroids has been associated with differences in childhood neurocognitive development, particularly when delivery occurs at term. 9–11 In some studies, exposure to antenatal corticosteroids has also been found to increase maternal infection morbidity. 6…”
mentioning
confidence: 99%
“…Recent research hints at potential long‐term neurodevelopmental challenges in children who have been exposed to corticosteroids 3 . There is also growing concern about severe infections, pointing to heightened risks.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies revealed the potential adverse effects of antenatal corticosteroid on fetal neurodevelopment and even contributed to mental and behavioral disorders in children. 12 , 13 Therefore, there is an urgent need to explore the exact aetiology and pathogenesis of GDM-induced FLUD.…”
Section: Introductionmentioning
confidence: 99%